2007
DOI: 10.1001/archinte.167.21.2345
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Depression, and Risk of Hospitalization and Mortality in Chronic Obstructive Pulmonary Disease

Abstract: Background:We sought to determine whether depressive or anxiety symptoms are associated with chronic obstructive pulmonary disease (COPD) hospitalization or mortality. These data were collected as part of the National Emphysema Treatment Trial (NETT), a randomized controlled trial of lung volume reduction surgery vs continued medical treatment conducted at 17 clinics across the United States between January 29, 1998, and July 31, 2002.Methods: Prospective cohort study among participants in the NETT with emphys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
151
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 56 publications
11
151
0
6
Order By: Relevance
“…20 Some studies have demonstrated only a weak association between psychological disturbance 22 or health-related quality of life 11 and mortality in COPD patients. Yet, depressive symptoms were found to be strong predictors for mortality (odds ratios ͓ORs͔, 1.9, 23 3.6, 24 and 2.7 25 ), independent of other disease severity and other risk factors, in COPD patients in three studies. It is noteworthy that two of the studies 23,24 focused on COPD patients who had been hospitalized for acute exacerbation.…”
Section: Original Researchmentioning
confidence: 90%
See 1 more Smart Citation
“…20 Some studies have demonstrated only a weak association between psychological disturbance 22 or health-related quality of life 11 and mortality in COPD patients. Yet, depressive symptoms were found to be strong predictors for mortality (odds ratios ͓ORs͔, 1.9, 23 3.6, 24 and 2.7 25 ), independent of other disease severity and other risk factors, in COPD patients in three studies. It is noteworthy that two of the studies 23,24 focused on COPD patients who had been hospitalized for acute exacerbation.…”
Section: Original Researchmentioning
confidence: 90%
“…The assessment of the depression symptoms was conducted during or shortly after (within 2 to 4 weeks) hospitalization for an exacerbation, which may have been reflected in increased the levels of depressive symptomatology. Only one study 25 demonstrated that adjusted depressive symptoms were associated with 3-year mortality and not with 1-year mortality in stable COPD patients. In contrast, two other studies 26,27 did not find an association between mortality and depression after adjustment for disease severity.…”
Section: Original Researchmentioning
confidence: 99%
“…Although many medical comorbidities play a role in respiratory decompensation and rehospitalization (22,23), the impact on readmissions of psychological comorbidities such as depression and anxiety, which are highly prevalent in patients with COPD and affect quality of life, remains largely unexplored (24,25). In small cohorts, data showed that depressive symptoms in patients with COPD predicted exacerbation risk over 1 year (26,27).…”
mentioning
confidence: 99%
“…Among patients with COPD, depression remains one of the most common, yet least recognized and undertreated, comorbidities, with a prevalence of 17-44% (21)(22)(23)(24)(25)(26)(27). Depression has been associated with decreased adherence to maintenance medications used in chronic conditions such as diabetes (28,29).…”
mentioning
confidence: 99%